Meconium Stained Liquor in Labor and Mode of Delivery: A Time for Reappraisal (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Meconium stained amniotic fluid (MSAF)during labor is a common almost daily encountered problem. Overall incidence of MSAF varies between 12% to 20%.Objective: To determine the mode of delivery in case of meconium stained liquor in labor.Methodology: This is a cross-sectional, observational study conducted in the Department of Obs. & Gynae, Shaheed Suhrawardy Medical College Hospital, Dhaka from January 2017 to June 2017. Sample size was 100 pregnant ladies who were admitted to the labor ward with ruptured membranes, are included in the study. The meconium-stained liquor was clinically assessed. Color of amniotic fluid and type of meconium was noted at the time of per vaginal examination.Result: The mean age of the study group was 32.3±6.4 years mostly in between 20 to 29 years. The gestational age of the study group was 37-40 weeks (41%) and 40-42 weeks (59%). Mean gestational week was 40.12±1.43. The meconium grade of the study group, grade I (48%), grade II (32%), and grade III (20%). The time of meconium was discovered latent 1st stage of labor (17.0%)-Grade I (35%), Grade II (23.5%), Grade III (23.5%), active 1st stage of labor (41.0%)- Grade I (48.7%), Grade II (29.26%), Grade III (21.95%) and 2nd stage of labor (42%)- Grade I (52.3%), Grade II (38.09%), Grade III (9. 5%).The mode of delivery was NVD (47.0%), Instrumental vaginal delivery (14%), and emergency C/S (39.0%). The time interval of delivery after discovering MSL was 0-2hour (59.0%), 2-4 hour (24%) and 4-6 hr. (17. 0%). Apgar score at one minute was found 7-10 in 22.5%,4 – 6 in 69.4% and 3 or less in 8.1%. Apgar score at five minute was found 7 – 10 in 69.4% 4-6 in 25.8%,3 or less in 4.8%. Fetal outcome was alive 98% and FSB 2%. Immediate resuscitation was needed for 62%.Conclusion: The thickly meconium stained group was significantly associated with higher cesarean rate. Delivered babies from this group need more immediate resuscitation. The thinly meconium stained group can be observed for vaginal delivery with adequate maternal and fetal monitoring.Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 71-77